Cortisol release from adipose tissue by 11beta-hydroxysteroid dehydrogenase type 1 in humans. - Stimson, R; Andersson, J; Andrew, R; Redhead, D; Karpe, F; Hayes, P; Olsson, T; Walker, B (2009)
OBJECTIVE: 11beta-Hydroxysteroid dehydrogenase type 1 (11beta-HSD1) regenerates cortisol from cortisone. 11beta-HSD1 mRNA and activity are increased in vitro in subcutaneous adipose tissue from obese patients. Inhibition of 11beta-HSD1 is a promising therapeutic approach in type 2 diabetes. However, release of cortisol by 11beta-HSD1 from adipose tissue and its effect on portal vein cortisol concentrations have not been quantified in vivo. RESEARCH DESIGN AND METHODS: Six healthy men underwent 9,11,12,12-[(2)H](4)-cortisol infusions with simultaneous sampling of arterialized and superficial epigastric vein blood sampling. Four men with stable chronic liver disease and a transjugular intrahepatic porto-systemic shunt in situ underwent tracer infusion with simultaneous sampling from the portal vein, hepatic vein, and an arterialized peripheral vein. RESULTS: Significant cortisol and 9,12,12-[(2)H](3)-cortisol release were observed from subcutaneous adipose tissue (15.0 [95% CI 0.4-29.5] and 8.7 [0.2-17.2] pmol . min(-1) . 100 g(-1) adipose tissue, respectively). Splanchnic release of cortisol and 9,12,12-[(2)H](3)-cortisol (13.5 [3.6-23.5] and 8.0 [2.6-13.5] nmol/min, respectively) was accounted for entirely by the liver; release of cortisol from visceral tissues into portal vein was not detected. CONCLUSIONS: Cortisol is released from subcutaneous adipose tissue by 11beta-HSD1 in humans, and increased enzyme expression in obesity is likely to increase local glucocorticoid signaling and contribute to whole-body cortisol regeneration. However, visceral adipose 11beta-HSD1 activity is insufficient to increase portal vein cortisol concentrations and hence to influence intrahepatic glucocorticoid signaling.